2021
DOI: 10.1002/fsn3.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat flour particle size on flour physicochemical properties and steamed bread quality

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Various factors can affect grain hardness, including environmental factors, grain storage conditions, grain protein content, kernel moisture content, and so on (Hrušková & Švec, 2009). Besides hardness, PSI is also affected by milling parameters such as the milling intensity (Pang et al., 2021). Overall, the PSI test helps millers and bakers classify wheat according to the degree of hardness, adjust tempering settings at the mill, and indicate the milling/baking performance and end‐product functionality (Acar et al., 2019; Bettge & Morris, 2000).…”
Section: Grain and Flour Properties From The End‐user Perspectivementioning
confidence: 99%
“…Various factors can affect grain hardness, including environmental factors, grain storage conditions, grain protein content, kernel moisture content, and so on (Hrušková & Švec, 2009). Besides hardness, PSI is also affected by milling parameters such as the milling intensity (Pang et al., 2021). Overall, the PSI test helps millers and bakers classify wheat according to the degree of hardness, adjust tempering settings at the mill, and indicate the milling/baking performance and end‐product functionality (Acar et al., 2019; Bettge & Morris, 2000).…”
Section: Grain and Flour Properties From The End‐user Perspectivementioning
confidence: 99%
“…The results obtained after ultra‐micromilling (<21 and <12 μm) of commercial flours (average particle size of ~75 μm) showed that the reduction in particle size distribution increased the elasticity, deformation resistance, hardness, adhesion, relaxation time, and tensile viscosity of the dough while decreasing the starch pasting enthalpy (Lazaridou et al ., 2018). In addition, the test results for wheat flour with a particle size distribution of 52.36–108.89 μm showed that reducing its particle size effectively increased the maximum tensile resistance, and samples with medium particle diameters (78 and 66 μm) exhibited the highest stretchability; the ratio of loss tangent (G″/G′) decreased with decreasing particle size (Pang et al ., 2021).…”
Section: Particle Size Distribution and Flour Qualitymentioning
confidence: 99%
“…Compared with Chinese buns made from wheat flour with larger particle size, those from wheat flour with smaller particle size were significantly smaller in specific volume, higher in hardness and chewiness, lower in elasticity, and showed no significant difference in adhesiveness. The quality of Chinese steamed buns was better when medium‐size grain flour (~78 μm) was used for preparation (Pang et al ., 2021). Grain size is the main factor affecting the quality traits of wheat flour.…”
Section: Particle Size Distribution and Flour Qualitymentioning
confidence: 99%
“…The intrinsic characteristics of flour are strongly influenced by particle size, which in turn affect the final quality of food product (Ahmed et al., 2019; Pang et al., 2021). Size reduction leads to increased surface area that affects the mixing, dough making and cooking parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Size reduction and particle size are supposed to be related with cell‐wall materials of the grains, and exhibits significant impact on quality characteristics (Ahmed et al., 2019). The effect of flour particle on flour quality of wheat (Pang et al., 2021), pumpkin (Ahmed et al., 2014), rice, (Kim & Shin, 2014), chestnut (Moreira et al., 2010; Ahmed et al., 2016a), oat (Gu et al., 2022), kidney bean (Sun et al., 2019), lentil (Ahmed et al., 2016b), quinoa (Ahmed et al., 2019), and pumpkin (Ahmed et al., 2014) was studied previously.…”
Section: Introductionmentioning
confidence: 99%